In-Silico Analysis of the BDNF (Brain Derived Neurotrophic Factor) Protein of Pigeon (Columba livia) - Ni Gusti Ayu Galuh Candra Kirana; I Made Budiarsa; I Nengah Kundera; Mohammad Jamhari (EduChemia (Jurnal Kimia dan Pendidikan), 2020)
BDNF protein plays a role in the growth and survival of neurons. BDNF protein has some uniqueness, and information on this protein is still limited reported, especially in pigeons. The purpose of this study is to predict the three-dimensional structure of the pigeon of  BDNF protein, to provide information in understanding the characteristics, structure of the protein using a homology approach through in-silico analysis. The BDNF protein is predicted using the SWISS-MODEL server and visualizing the prediction results on the CHIMERA Software. Pigeon BDNF protein was taken from Uniprot with a B4Z8Q access codewith a template of 1b8m.1. The analysis shows that BDNF protein has  an identity of 93,20% consisting of 226 amino acids with a target QMEAN value of -0.17 and hydrophobic amino acids namely Trp, His, Tyr, Ile, Leu, Gly, Lys, Cys, Ala, Phe, Met, and Val. Carboxyl residues, namely Glu, Asp and Val, and amine residues, namely Lys and Ser, with 82 hydrogen bonds.